Application and research progress of CO2 capture and utilization technology - HE Zhiyong,GUO Benshuai,WANG Dong,MAO Songbai,LI Zhongyu (Youqicang pingjia yu kaifa)
The global consensus on achieving carbon neutrality is driven by the urgent need to address climate change caused by excessive CO2 emissions. Carbon Capture, Utilization, and Storage（CCUS） stands out as a critical solution, receiving significant attention from the researchers. Sinopec Nanjing Research Institute of Chemical Industry Co., Ltd. has been committed to the research and development and application of CO2 capture and utilization technology for a long time. The institute has perfected three advanced carbon capture methods: low partial pressure flue gas carbon capture technology, NCMA（Nanjing chemical mixed amine） decarburization technology and catalytic hot potassium alkali decarburization technology, which have been successfully applied in many industrial projects. Furthermore, the institute is pushing boundaries in new carbon capture and CO2 utilization technologies, achieving notable advancements that align with both domestic and international standards.